Pivoting Higher Education to Teach Sustainability - Bourqui, Dominique; Claivaz, David (International Transitions, 2024)
Education institutions worldwide are launching an ever-growing number of initiatives to teach sustainability. The UN refers to the field in which these initiatives occur as the field of Education for Sustainable Development (ESD). The acronym HESD is used in reference to Higher Education for Sustainable Development. No authoritative description of HESD has yet emerged that would provide clear criteria in the field describing what Higher Education for Sustainable Development should comprise. In our paper, we introduce a simple typology to differentiate (1) the discussion and definition of sustainability, sustainable development, and sustainability related concepts, from (2) the commitment to sustainability, and from (3) the ‘making of sustainability’, as possible dimensions of sustainability education leads to understanding that a change leads to understanding that a change, taking the form of a pivot, is needed to teach the third dimension. We explain the pivot operated by Business School Lausanne (BSL) and why BSL has chosen to operate this pivot by associating sustainability and Entrepreneurship education. We then describe three concrete initiatives that have been taken, for which BSL has pivoted its educational approach: (1) Learning through real-life projects in sustainability: Consulting week for an association “Les Paniers de la Mule” (2) Sustainability in residence: MyBluePlanet (3) The Academic Citizens’ Assembly. Business School Lausanne (BSL) is a private Swiss business School. BSL’s engagement towards sustainability dates back more than a decade ago, when BSL committed in 2006 to the UN Global Compact Ten Principles and became in 2010 a Principles for Responsible Management Education (PRME) member.